Структурно-фазовое состояние продуктов экзотермической реакции титан-полиэтилентерефталат - Матвеев, Алексей Евгеньевич (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
Plastic pollution is one of the most pressing environmental problems, and a huge amount of effort and money is directed towards solving it. The main component of all plastic materials (CxHy) is carbon. In the present study the phase composition and structure of the reaction products Ti + C10H8O4 (polyethylene terephthalate) are studied. It is established that the phase composition of the reaction products depends on the concentration ofplastic chips in the initial mixture. Increase of the plastic in the mixture to 35 wt. % leads to the formation of pure titanium carbide, the average particle size of which is 1.2 microns. The results obtained will help create the basis for the development of a fundamentally new, cost-effective technology for processing plastic waste into carbides and carbide-containing materials.